The effect of vitamin D deficiency during pregnancy on adverse birth outcomes in neonates: a systematic review and meta-analysis - You, Zhiying; Mei, Hua; Zhang, Yayu; Song, Dan; Zhang, Yanbo; Liu, Chunli (Frontiers in Pediatrics, 2024)
Objective：To systematically evaluate the effect of vitamin D deficiency during pregnancy on neonatal adverse outcomes, such as preterm infants, low birth weight infants (LBWI), and small for gestational age (SGA) infants.Methods： A comprehensive literature search was conducted across multiple databases including PubMed, Embase, Cochrane Library, SinoMed, Wanfang Data Knowledge Service Platform, China National Knowledge Internet (CNKI), and VIP Chinese Science and Technology Journal Database (VIP). Following predefined inclusion and exclusion criteria, two researchers independently screened, extracted data, and assessed the quality of the included studies. Meta-analysis was performed using RevMan 5.4 and Stata 14 software to synthesize the findings.Results：This study incorporated 13 cohort studies from 8 different countries and regions, encompassing a total of 55,162 pregnant women, among whom 28,155 were identified as having vitamin D deficiency. The Newcastle-Ottawa Scale (NOS) score ranged from 7 to 9 points. Metaanalysis results indicated a higher incidence of LBWI(OR=5.52, 95%CI=1.31~23.22. P=0.02) in the group of pregnant women with vitamin D deficiency compared to those with adequate levels.However, there was no statistically significant difference in the likelihood of premature birth(OR=1.25, 95%CI=0.78~1.99. P=0.36) or small for SGA(OR=1.47, 95%CI=0.81~2.68. P=0.21) among newborns born to mothers with vitamin D deficiency versus those with sufficient levels of vitamin D. Subgroup analysis based on the timing of maternal blood collection revealed that there was no statistically significant association between vitamin D levels during pregnancy and the incidence of preterm birth across all stages of pregnancy. Furthermore, vitamin D deficiency throughout the entire pregnancy was associated with an increased incidence of neonatal LBWI, whereas vitamin D levels during the first, second, and third trimesters did not demonstrate statistically differences on LBWI. Neonates born to mothers with vitamin D deficiency throughout pregnancy were found to have a higher likelihood of developing SGA. However, there was no statistically significant association between vitamin D levels and the development of SGA during the first and second trimesters.Conclusions：Adequate levels of vitamin D during pregnancy may decrease the incidence of LBWI, although further research is needed to determine its impact on the occurrence of preterm birth and SGA.